2016
DOI: 10.1371/journal.pone.0160920
|View full text |Cite
|
Sign up to set email alerts
|

Differential microRNA Expression and Regulation in the Rat Model of Post-Infarction Heart Failure

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…[ 42 47 ]. Therefore, dysregulation of (a) microRNA(s) due to extrinsic and/or intrinsic stress further adds to the severity of the disease [ 48 50 ]. This very fact can and is being capitalized for the potential therapeutic uses of microRNAs against cardiac diseases [ 43 , 48 , 51 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 47 ]. Therefore, dysregulation of (a) microRNA(s) due to extrinsic and/or intrinsic stress further adds to the severity of the disease [ 48 50 ]. This very fact can and is being capitalized for the potential therapeutic uses of microRNAs against cardiac diseases [ 43 , 48 , 51 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 13 candidate miRNAs are predicted to interact with 8 out of the 45 proteins modulated by LVR [10], testifying that they are involved in LVR after MI. Moreover, 9 out of the 13 candidate miRNAs have been described as biomarkers of HF: miR-21-3p, miR-21-5p, miR-23a-3p, miR-29b-3p, miR-122, miR-133a, miR-145-5p, miR-222-3p and miR-320a [10,[15][16][17][18][19], confirming their potential as targets to predict HF ( Figure 1A). To prioritize candidate miRNAs with high relation specificity with LVR, we evaluated in vivo the association of the 13 candidate miRNAs with LVR after MI ( Figure 1B).…”
Section: Analysis Of the Protein-mirna Network Derived From Post-mi Rmentioning
confidence: 68%
“…A previous study has shown that MiR-31a-5p is linked to colorectal cancer (23). Our more recent work revealed that the miR-31a-5p level was significantly higher in the hearts of rats with post-infarction HF than that in the sham group (24). However, the exact role of miR-31a-5p in the pathogenesis of HF remains uncertain.…”
Section: Introductionmentioning
confidence: 85%